2013
DOI: 10.3138/cjccj.2012.es01
|View full text |Cite
|
Sign up to set email alerts
|

Three Decades of Public Attitudes Research on Crime and Punishment in Canada

Abstract: Three decades of research on public perceptions in Canada has fundamentally shifted academic and policy approaches to understanding public views of crime and punishment. The contributions of Anthony Doob and his colleagues have influenced methodology, such as the inclusion of experimental design, and have supported an underlying commitment to understanding the public's view of crime and its relationship to policy. This article examines key findings coming out of this body of research and the impact of this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It has also been suggested that to reform public opinion about general punishment policies, the justice system should do more to engage and educate the public (Roberts, 1992). In this regard, it has been proposed that one way to reduce support for punitive policies is to remind the public about the human characteristics and individuality of actual offenders (Indermaur, 1987; Varma & Marinos, 2013). The results of the present studies provide empirical support for this argument.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that to reform public opinion about general punishment policies, the justice system should do more to engage and educate the public (Roberts, 1992). In this regard, it has been proposed that one way to reduce support for punitive policies is to remind the public about the human characteristics and individuality of actual offenders (Indermaur, 1987; Varma & Marinos, 2013). The results of the present studies provide empirical support for this argument.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the omnibus crime bill Safe Streets and Community Act was tabled in the months before the 2011 election that resulted in a Conservative majority mandate. The bill faced deep criticism because buried in its 110 pages was a fundamental shift in the federal government's approach to crime (Brennan, 2012; CCLA, 2010: 1; Cook and Roesch, 2012; Doob, 2014; Statistics Canada, 2011; Varma and Marinos, 2013).…”
Section: Legislative Debatementioning
confidence: 99%
“…It is well-known that providing the public with more information about specific cases improves people’s confidence in the fairness of the criminal justice system and elicits less punitive responses (Cullen et al, 2000; Gelb, 2006; Roberts and Hough, 2005; Varma and Marinos, 2013; Warner et al, 2017). However, providing research participants with sufficient information to elicit truly informed opinion can be challenging.…”
Section: Introductionmentioning
confidence: 99%